Solutions for Destination Management on Agri-Tourism Farm - Ioan Petroman; Cornelia Petroman; Diana Marin; Constantin Buzatu; Adrian Dumitrescu; Ştefan Coman; Andreea Stan; Daniela Avramescu (Scientific Papers Animal Science and Biotechnologies, 2023)
Farm tourism can be an alternative to agricultural jobs in rural communities with real agri-tourism potential. To improve destination management, we need to implement a type of management based on knowledge management. A second type of management that is a must in farm tourism is the integrated management of agri-tourism destination quality based on a code of good practices in the integrated management of quality. In order to improve agri-tourism management quality, we need to apply best management practices, i.e. 15 basic principles that contribute to the improvement of farm tourism management. These three types of management, if implemented on any agri-tourism farm, can contribute to the improvement of destination management.